Synthesis, characterization and anticancer activity of gold(III) complexes with (1R, 2R)-(−)-1, 2-diaminocyclohexane. (14th December 2015) - Omer, Khalid H.; Seliman, Adam A.; Altaf, Muhammad; Casagrande, Naike; Aldinucci, Donatella; Altuwaijri, Saleh; Isab, Anvarhusein A.
Graphical abstract: Two gold(III) complexes, [(DACH)AuCl2 ]Cl and [(DACH)2 Au]Cl3, derived from (1 R, 2 R )-(−)-1, 2-diaminocyclohexane and NaAuCl4 were synthesized and characterized using different physical methods. In vitro studies of these complexes have been reported here. Abstract: Two gold(III) complexes, [(DACH)AuCl2 ]Cl (1 ) and [(DACH)2 Au]Cl3 (2 ), derived from (1 R, 2 R )-(−)-1, 2-diaminocyclohexane and sodium tetrachloroaurate dihydrate, NaAuCl4 ·2H2 O, were synthesized and fully characterized using elemental analysis and different physical methods, such as FTIR, 1 H NMR, 13 C NMR, solid-state NMR and X-ray crystallography. The data confirm the coordination of the DACH ligand to the gold(III) metal centre through its nitrogen atoms. According to in vitro cytotoxic studies, complex2 was more effective against the three human tumor cell lines evaluated (the ovarian cancer cell line A2780, its cisplatin-resistant clone A2780cis and the classical Hodgkin lymphoma cell line L-540). The fold-resistance of the A2780 and A2780cis cells to cisplatin was about twofold lower for both gold(III) complexes.